Bùi Ân Hậu
Giới thiệu về bản thân
Chào mừng bạn đến với trang cá nhân của Bùi Ân Hậu
0
0
0
0
0
0
0
2024-10-25 12:31:03
a)A+B
= (x²—3xy—y²+1)+(2x²+y²—7xy—5)
=x²—3xy-y²+1+2x²+y²—7xy—5
=(x²+2x²)+(-3xy—7xy)+(-y²+y²)+(1—5)
=3x²+(-4xy)+(-2y²)+(-4)
=3x²—4xy—2y²—4
b)Để tìm đa thức C biết C+A—B=0 ta có:
C+(x²—3xy—y²+1)—(2x²+y²—7xy—5)=0
C+x²—3xy—y²+1—2x²—y²+7xy+5=0
C+(x²—2x²)+(—3xy+7xy)+(‐y²—y²)+(1+5)=0
C+(-x²)+4xy+(-2y²)+6=0
C=x²—4xy+2y²—6
c)C=x²—4xy+2y²—6 với x=2;y=-1/2 ta có:
C=2²—4.2.(-1/2)+2.(-1/2)²—6
C=4—(-4)+1/2—6
C=2+4+1/2—6
C=5/2